The relationship between parental awareness and self-efficacy with defecation control skills in Iranian toddlers - Zahra Janat Alipour; Amaneh Mahmoudian; Fatemeh Larijani; Zahra Fotokian; Nasrin Navabi; Fatemeh Mohammadkhah (Shahrekord University of Medical Sciences, 2023)
Background and aims: Toddlerhood is an important period of a child's development to master the functioning of the bowel and bladder sphincters. In this regard, the present study aimed to determine the relationship between parental awareness, self-efficacy, and defecation control skills in Iranian toddlers. Methods: The present study was descriptive cross-sectional research. The questionnaires on Demographic information of children and parents, parental awareness and self-efficacy, and defecation control skills were completed by 72 mothers of children aged 18-24 months old in the city of Ramsar. The data were analyzed using SPSS 18, descriptive tests of mean and standard deviation, analytical tests of analysis of variance, independent t-test, and Pearson's correlation coefficient. Results: The results showed that the awareness and self-efficacy level was at a medium level of 17.70±2.9230.54±7.15, and their children's defecation control skill was at a high level8.88±2.91 respectively. Also, there was a positive significant relationship between parental awareness (r=0.19, P=0.02) and self-efficacy (r=0.20, P=0.01) with defecation control skills. There was a significant relationship between the mother's occupation (P=0.04), the father's age (P=0.04), and parental self-efficacy (P=0.04). In addition, a significant relationship was found between the child's age (P=0.03) and the mother's age (P=0.01) with the child's defecation control skill. Conclusion: Promoting awareness and self-efficacy in training defecation control skills is a necessity for parents, and the policymakers should include the integrated care of children in the educational programs of the Ministry of Health so that it is included in the agenda of routine care of health centers in the country.